2022
DOI: 10.13057/biodiv/d230357
|View full text |Cite
|
Sign up to set email alerts
|

Extraction and characterization of sodium alginate from three brown algae collected from Sanur Coastal Waters, Bali as biopolymer agent

Abstract: Abstract. Permatasari AAAP, Rosiana IW, Wiradana PA, Lestari MD, Widiastuti NK, Kurniawan SB, Widhiantara IG. 2022. Extraction and characterization of sodium alginate from three brown algae collected from Sanur Coastal Waters, Bali as biopolymer agent. Biodiversitas 23: 1655-1663. Sodium alginate extracted algae are gaining attention as alternative biopolymer materials. This research aimed to extract and characterize the natrium alginate from three brown algae obtained from Sanur Beach, Denpasar, Bali, Indones… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 49 publications
1
5
0
Order By: Relevance
“…Moreover, the obtained yield was higher compared with other Cystoseira species, such as the Tunisian C. barbata (9.9%) [17] and C. sedoides alginate (11%) [18]. The alginate content of C. crinita algae determined in this study was similar to that found for other brown algae from different botanical genera such as Dictyota (D. dichotoma and D. ciliolata 20-21%), Sargassum (S. fluitans 21.1-22.8% and S. oligocystum 18.9-20.5%), Padina (P. boergesenii 24.3% and P. gymnospora 21.5%), Turbinaria (T. triquetra 22% and T. ornata 20.2%), [27][28][29][30]. Nevertheless, Bulgarian Black Sea alginate had a lower extraction yield compared with the species used for the industrial production of alginate, such as Durvillaea willana and D. antarctica (44-53%), Macrocystis pyrifera (43%), Laminaria digitata (40%), and Ecklonia cava (35-38%) [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, the obtained yield was higher compared with other Cystoseira species, such as the Tunisian C. barbata (9.9%) [17] and C. sedoides alginate (11%) [18]. The alginate content of C. crinita algae determined in this study was similar to that found for other brown algae from different botanical genera such as Dictyota (D. dichotoma and D. ciliolata 20-21%), Sargassum (S. fluitans 21.1-22.8% and S. oligocystum 18.9-20.5%), Padina (P. boergesenii 24.3% and P. gymnospora 21.5%), Turbinaria (T. triquetra 22% and T. ornata 20.2%), [27][28][29][30]. Nevertheless, Bulgarian Black Sea alginate had a lower extraction yield compared with the species used for the industrial production of alginate, such as Durvillaea willana and D. antarctica (44-53%), Macrocystis pyrifera (43%), Laminaria digitata (40%), and Ecklonia cava (35-38%) [31][32][33].…”
Section: Discussionsupporting
confidence: 89%
“…The addition of 1% HCl is also a factor in decreasing the value of the ash content [41]. The ash content of research conducted by Permatasari, et al [40] is 17.34%. Meanwhile, in the research of Mushollaeni [46] and Septiani et al [45], the resulting ash content of sodium alginate is 28.59% and 31.24%.…”
Section: Ash Contentmentioning
confidence: 99%
“…e marine environment is currently considered as one of the most important sources in the eld of natural products research, as marine organisms have demonstrated extraordinary biological, biochemical, and biosynthetic potential (Newman and Cragg, 2014). Research into marine natural products is o en considered important for the identi cation of new chemical structures, especially those with unconventional mechanisms of action (Permatasari et al, 2022;. e relationship between macroalgae and their endophytic fungus has been reported in the ecological eld.…”
Section: Introductionmentioning
confidence: 99%